Marfan Syndrome with Bilateral Retinal Detachment - Shrestha, Chunu; Shrestha, Varun (Medical Journal of Shree Birendra Hospital, 2015)
Marfan syndrome is an autosomal dominant systemic disorder of connective tissue. Marfan syndrome affects most organs and tissues, especially the skeleton, lungs, eyes, hearts, and the large blood vessels. It is described by Antoine Marfan in 1896. Aortic root aneurysm and ectopia lentis are the cardinal features. In the absence of family history, the presence of these two manifestations is sufficient for confirmatory diagnosis of Marfan syndrome. Patient with ocular manifestations should be screened for cardiac involvement to support diagnosis. Retinal detachment is a potentially dangerous manifestation for its sight threatening nature. There is no cure for Marfan syndrome, so treatment focuses on managing the symptoms and reducing the risk of complications. Recent advances in diagnosis, improved surgical technique and application of prophylaxis has contributed in preservation of sight in such patients.